P Penentuan Nilai Sun Protecting Factor (SPF) Dan Uji Karakteristik Sifat Fisik-Kimia Sediaan Nanoherbal Bedak Dayak: Penentuan Nilai Sun Protecting Factor (SPF) Dan Uji Karakteristik Sifat Fisik-Kimia Sediaan Nanoherbal Bedak Dayak - Wahyu Nugroho; Noverda Ayuchecaria; Saftia Aryzki (Jurnal Pelayanan Kefarmasian dan Sains, 2022)
Background: One of the local wisdom products that is widely used by the Dayak community to reduce the adverse effects of sunlight is Dayak powder or cold powder. Made from rice mixed with several local herbs, Dayak powder is used to treat skin health and beauty. Dayak powder has the potential to be an alternative to protect skin health from the threat of UV radiation. In this study, the sample used was in the form of nanoparticles. Utilization of technology in the field of nano materials is expected to be able to improve its bioactivity performance and comfort of use when compared to conventional Dayak powder Objective: This study aims to determine the activity of sunscreen and the physico-chemical characteristics of Dayak powder nanoherbal preparations. Methods: The sunscreen activity test was carried out in vitro using UV-Vis spectrophotometry. Determination of the value of the sun protection factor (SPF) is read at a wavelength of 290-320nm. In addition, the physico-chemical characteristics of the preparation were also tested including organoleptic, homogeneity, pH, dispersion and adhesion. Results: The test results obtained that the SPF value of nanoparticle-sized Dayak powder at a concentration of 200 and 400 ppm was in the minimal protection category (SPF 1-4 value) while for a concentration of 600ppm both were in the medium protection category (SPF value 4-6). The results of the test of orgoleptis characteristics and homogeneity did not change until day 14. The pH test showed the result of 5.87. The dispersion test without load showed an average diameter of 2.47 cm and adhesion of 2.33 seconds. Conclusion: The SPF value obtained at a concentration of 400ppm is in the moderate protection category. The preparation meets the requirements of organoleptic, homogeneity, pH, dispersion and adhesion